Acute kidney injury (AKI) associated with intravenous aciclovir in adults: Incidence and risk factors in clinical practice. (September 2018) - Ryan, Lucy; Heed, Andrew; Foster, Jonathan; Valappil, Manoj; Schmid, Matthias L.; Duncan, Christopher J.A.
Highlights: No studies have assessed risk factors for aciclovir-associated acute kidney injury (AKI) in adults. AKI occurred in 13% of parenteral aciclovir treatment episodes, half were grade 2/3 by KDIGO criteria. Baseline chronic kidney disease and total dose were significant independent risk factors for AKI. These data reinforce the importance of dose adjustment for baseline renal function and ideal body weight. Abstract: Objectives: This study sought to identify the incidence of, and risk factors for, acute kidney injury (AKI) in adults treated with parenteral aciclovir. Methods: A single-centre retrospective cohort study of prospectively acquired electronic clinical, pharmacy and laboratory data was performed with approval of the Caldicott guardian. AKI was defined by Kidney Disease Improving Global Outcomes (KDIGO) criteria, prior to analysis of baseline patient and treatment-related risk factors. Results: 269 aciclovir treatment episodes were identified in 268 patients. Overall incidence of AKI was 13%. Half of AKI episodes were KDIGO grade 2/3. In univariate analysis, AKI occurred more frequently in patients with pre-existing chronic kidney disease (CKD), diabetes, and in patients treated with higher daily doses of aciclovir. There was also a trend to increased age in patients with AKI. In a binomial logistic regression model only CKD and daily dose remained significant independent factors. Conclusions: AKI is an important side effect of parenteral aciclovir, the incidence of which is comparable to established nephrotoxic drugs such as aminoglycosides. Patients with pre-existing chronic kidney disease or receiving higher total doses are at greatest risk, reinforcing the clinical importance of appropriate dose adjustment for ideal body weight and baseline renal function.